Cell and animal models in aging and dementia research - Hoyer, Siegfried; Müller, Dorothea; Plaschke, Konstanze (Springer, 1994)
Although age has been recognized as a risk factor for late-onset dementia of Alzheimer type, its etiology is unknown as yet. Several age-related metabolic abnormalities may thus become important for the pathogenesis of the late-onset form. Studies at the cellular/molecular level in brain tissue are possible post mortem, but lack information on the beginning of the disorder. In this supplement, different approaches are dealt with how to induce structural and/or metabolic abnormalities in relevant cell cultures, in brain slices and in experimental animals, and how behavioral changes parallel the metabolic variations
Keywords: Konferenzschrift -- 1993 -- Heidelberg; Neuropathologie; Demenz; Tiermodell; Altern; Zellkultur